La chevelure de sainte Marie l’Égyptienne d’après Rutebeuf. - Daniela Mariani (Perspectives Médiévales)
In Rutebeuf’s Vie de sainte Marie l’Égyptienne there is an incoherence in the description of the saint’s physical aspect. The hair is lying on her shoulders (v. 447) but, at the time of her death, they turn out to be a shroud (v. 1136). The detail of the hair adds a new element to the sources’ issue: Rutebeuf seems to have used both the so called T version and the version in prose named O. This philological issue will be tackled by looking at the figurative images of the Aegyptica and to the “femme sauvage” character. The analysis is a great challenge also from a methodological point of view: the consultation of an iconographic corpus for the comprehension of a text and the rebuilding of the audience’s horizon of expectations.